Pengembangan Flipbook EMOSA PANDADI sebagai Media Pembelajaran Interaktif dalam Meningkatkan Literasi Menulis Pantun Siswa Kelas V SD - Setiawaty, Rani; Ramadhina, An Nissa Rizki; Tabina, Melia Hansa Cordelia; Taqwa, Aldino Khoirozadit (Lembaga Yasin AlSys, 2025)
The low ability of primary school students to write pantun (traditional Indonesian poetry) remains a major issue, primarily due to a lack of understanding of pantun structure and rules, the dominance of conventional teaching methods, limited use of interactive media, and minimal integration of local values into learning materials. This study aims to develop and evaluate the feasibility of an interactive digital learning medium named EMOSA PANDADI (E-Modul Sastra Pantun dengan Kearifan Lokal Purwodadi) to enhance pantun writing literacy among fifth-grade students. The research employs a Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Validation was conducted by subject matter and media experts, along with practicality testing by teachers and students. Validation results indicate that the media is highly feasible, with an average score of 4.6 from content experts and 4.2 from media experts. Teacher responses yielded an average score of 4.5, while student learning outcomes improved from a pretest score of 58 to a posttest score of 86, with an N-Gain value of 0.66, categorized as moderate to high. Students also responded very positively, with an average score of 4.5. The study concludes that the EMOSA PANDADI flipbook is both effective and suitable for use in Indonesian language instruction, particularly in pantun writing. The media not only improves learning outcomes but also fosters literacy enthusiasm through an interactive, enjoyable, and culturally grounded approach, making it highly relevant for promoting independent learning and strengthening student character.